A History of Exploitation of the Colonised in Northern Nigeria During the Influenza Pandemic of 1918-1919 - Itodo, Unekwu Friday (African historical review, 2023)
The 1918 influenza pandemic was a devastating event that killed millions of people around the world. In Northern Nigeria, the pandemic was particularly deadly, and the British colonial administration's response to the crisis was characterised by exploitation and neglect. This article examines a variety of historical sources, including letters, memoirs, and reports written by British colonial officials in Northern Nigeria during the pandemic. The study adopts the theory of dependency. The article finds that the colonial government exploited the colonised people of Northern Nigeria during the pandemic. The article argues that the colonial government's exploitation during the pandemic was a clear example of their disregard for the lives and well-being of the people they governed. It also argues that the pandemic provides a valuable lens through which to examine the ways in which colonial powers prioritised their own interests over the well-being of those they ruled during times of crisis. The article concludes by calling for further research on the exploitation of the colonised during the influenza pandemic and other historical crises.